2019
DOI: 10.7150/thno.35972
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of glycyrrhizin and doxorubicin by alginate nanogel particles attenuates the activation of macrophage and enhances the therapeutic efficacy for hepatocellular carcinoma

Abstract: Nanocarrier drug delivery systems (NDDS) have been paid more attention over conventional drug delivery system for cancer therapy. However, the efficacy is hampered by the fast clearance of activated macrophage from the blood circulation system. In this study, glycyrrhizin (GL) was introduced into alginate (ALG) nanogel particles (NGPs) to construct multifunctional delivery vehicle to decrease the fast clearance of activated macrophage and enhance the anticancer efficacy with the combination therapy of GL and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 52 publications
3
35
0
1
Order By: Relevance
“…38,39 Combination therapy is increasingly used to treat cancer. 40 Recently, many studies have used nano-delivery systems to codeliver chemotherapeutics and chemosensitizers for tumor therapy. Wang et al revealed that the co-delivery of DOX and CUR polymeric micelles can improve anti-tumor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Combination therapy is increasingly used to treat cancer. 40 Recently, many studies have used nano-delivery systems to codeliver chemotherapeutics and chemosensitizers for tumor therapy. Wang et al revealed that the co-delivery of DOX and CUR polymeric micelles can improve anti-tumor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Nanogels provide a platform for drug codelivery, which is attributed to their 3D network structure for incorporating with both hydrophilic and hydrophobic compounds. In a recent study, both glycyrrhizin (GL) and DOX were encapsulated into alginate (ALG) nanogel particles via the phase inversion temperature emulsification method; the obtained drug-loaded alginate nanogels (DOX/GL-ALG NGPs) exhibited not only the hepatocellular carcinoma targeting property by GL, but also the synergistic antitumor effects of GL and DOX ( Figure 9) [107]. In addition, ALG nanogels also presented favorable biocompatibility and low toxicity to hepatic tissues by controlled drug release [108].…”
Section: Combinational Chemotherapymentioning
confidence: 99%
“…In HCC, TAM and Kupffer cells are characteristic immunosuppressive factors that mediate tumor evasion; the abundance of these cells is a negative biomarker for HCC prognosis. Wang et al [43] found that the intravenous administration of glycyrrhizin regulated the Bax/Bcl-2 ratio and caspase-3 activity, leading to Kupffer cell inactivation. Tumor immunity is consequently enhanced by the attenuation of the suppressive function of Kupffer cells and TAMs.…”
Section: Tcms Downregulate Immunosuppressive Factors Tomentioning
confidence: 99%